About stability of levitating states of superconducting myxini of plasma traps-Galateas - Bishaev, A.M.; Bush, A.A.; Gavrikov, M.B.; Denis’uk, A.I.; D’yakonitsa, O.Y.; Kamentsev, K.Y.; Kozintseva, M.V.; Kolesnikova, T.G.; Savelyev, V.V.; Smirnov, P.G.; Shapovalov, M.M.; Voronchenko, S.A. (Вопросы атомной науки и техники, 2015)
To develop a plasma trap with levitating superconducting magnetic coils it is necessary to carry out the search of their stable levitating states. With this purpose, based upon the superconductor property to conserve the trapped magnetic flux, in the uniform gravitational field the analytical dependence of the potential energy of one or two superconducting rings, having trapped the given magnetic fluxes, in the field of the fixed ring with the constant current from the coordinates of the free rings and the deflection angle of their axes from the common axis of the magnetic system has been obtained in the thin ring approximation. Under magnetic fluxes of the same polarity in coils the existence of the found from the calculations equilibrium levitating states for the manufactured HTSC rings stable relative to the vertical shifts of levitating rings and to the deflection angle of their axes from the vertical has been confirmed experimentally. Для разработки плазменной ловушки с левитирующими сверхпроводящими магнитными катушками нужно выполнить поиск их устойчивых левитирующих состояний. С этой целью, исходя из свойства сверхпроводников сохранять захваченный магнитный поток, в однородном поле силы тяжести в приближении тонких колец получена аналитическая зависимость потенциальной энергии одного либо двух сверхпроводящих колец, захвативших заданные магнитные потоки, в поле закрепленного кольца с постоянным током от координат свободных колец и углов отклонения их осей от общей оси системы. При совпадающих по знаку потоках в кольцах существование найденных из расчетов равновесных левитирующих состояний для изготовленных ВТСП колец, устойчивых по отношению к вертикальным смещениям левитирующих колец и к отклонению их осей от вертикали, было подтверждено экспериментально. Для розробки плазмової пастки з левітуючими надпровідними магнітними котушками потрібно виконати пошук їх стійких левітуючих станів. З цією метою, виходячи з властивості надпровідників зберігати захоплений магнітний потік, в однорідному полі сили тяжіння в наближенні тонких кілець отримана аналітична залежність потенційної енергії одного або двох надпровідних кілець, які захопили задані магнітні потоки, у полі закріпленого кільця з постійним струмом від координат вільних кілець і кутів відхилення їх осей від загальної осі системи. При співпадаючих за знаком потоках у кільцях існування знайдених з розрахунків рівноважних левітуючих станів для виготовлених ВТНП кілець, стійких по відношенню до вертикальних зміщень левітуючих кілець і до відхилення їх осей від вертикалі, було підтверджено експериментально.